2012
DOI: 10.1007/s10340-012-0418-1
|View full text |Cite
|
Sign up to set email alerts
|

Euzophera bigella (Zeller) (Lepidoptera: Pyralidae) and Dasineura oleae (F. Low) (Diptera: Cecidomyiidae): Emerging olive crop pests in the Mediterranean?

Abstract: The olive is one of the most important crops in Greece as in many Mediterranean countries. Several insects are considered serious pests of the olive crop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Global climate change is influencing the geographical distributions and phenology of many insect species [13] , [14] , [15] , [16] , some of which are major crop pests. Such changes will inevitably lead to the appearance of new pests in some areas and changes to the biology of well established pests in others [17] , [18] , [19] , [20] , Guo et al [21] found that higher temperatures can lead to earlier egg hatching and eclosion in three Inner Mongolian grasshopper species [ Dasyhippus barbipes (Fischer de Waldheim), Oedaleus asiaticus B. Bienko, and Chorthippus fallax (Zubovsky)], which will likely extend their distribution northward as climate change continues. Another good example is the diamondback moth.…”
Section: Introductionmentioning
confidence: 99%
“…Global climate change is influencing the geographical distributions and phenology of many insect species [13] , [14] , [15] , [16] , some of which are major crop pests. Such changes will inevitably lead to the appearance of new pests in some areas and changes to the biology of well established pests in others [17] , [18] , [19] , [20] , Guo et al [21] found that higher temperatures can lead to earlier egg hatching and eclosion in three Inner Mongolian grasshopper species [ Dasyhippus barbipes (Fischer de Waldheim), Oedaleus asiaticus B. Bienko, and Chorthippus fallax (Zubovsky)], which will likely extend their distribution northward as climate change continues. Another good example is the diamondback moth.…”
Section: Introductionmentioning
confidence: 99%
“…In Greece, the polyphagous moth Euzophera bigella (Zeller) (Lepidoptera: Pyralidae) was noticed for the first time infesting the olive tree in 2011. Strong infestations were recorded in the province of Amphipolis with few cases of tree death [100]. The reasons for this outbreak were not investigated; however, Simoglou et al (2012) [100] hypothesized a combination of climate alterations as the main driver.…”
Section: Olive Mothsmentioning
confidence: 99%
“…Strong infestations were recorded in the province of Amphipolis with few cases of tree death [100]. The reasons for this outbreak were not investigated; however, Simoglou et al (2012) [100] hypothesized a combination of climate alterations as the main driver.…”
Section: Olive Mothsmentioning
confidence: 99%
See 2 more Smart Citations